2004
DOI: 10.1074/jbc.m403116200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Autoinhibition of the Plasma Membrane Ca2+ Pump by Substitution of Aspartic 170 by Asparagine

Abstract: The plasma membrane calcium ATPase (PMCA) actively transports Ca 2؉ from the cytosol to the extra cellular space. The C-terminal segment of the PMCA functions as an inhibitory domain by interacting with the catalytic core. Ca 2؉ -calmodulin binds to the C-terminal segment and stops inhibition. Here we showed that residue Asp 170 , in the putative "A" domain of human PMCA isoform 4xb, plays a critical role in autoinhibition. In the absence of calmodulin a PMCA containing a site-specific mutation of D170N had 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…In the presence of 1 M Ca 2ϩ the activity of the BFP-PMCA-GFP enzyme in the absence of calmodulin was ϳ40% of that attained at saturating concentrations of calmodulin. This value of basal activity is similar to that of the recombinant wild-type hPMCA4xb enzyme obtained from yeasts under similar conditions (19). These results suggest that the inhibitory function of the C-terminal regulatory domain was preserved despite the addition of the GFP.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In the presence of 1 M Ca 2ϩ the activity of the BFP-PMCA-GFP enzyme in the absence of calmodulin was ϳ40% of that attained at saturating concentrations of calmodulin. This value of basal activity is similar to that of the recombinant wild-type hPMCA4xb enzyme obtained from yeasts under similar conditions (19). These results suggest that the inhibitory function of the C-terminal regulatory domain was preserved despite the addition of the GFP.…”
Section: Resultssupporting
confidence: 69%
“…Thus, the most important point of interest was to investigate which step of the BFP-PMCA-GFP activation was being reported by the decrease in FRET. For this purpose we took advantage of the activating effect of mutation D170N reported previously (19). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in ATP7B, the fifth and sixth NMBDs connected to the Ma helix are relatively important for enzymatic property (51). In a class of PII-ATPases, including plasma membrane Ca 2ϩ -ATPase, a regulatory domain is attached to the C terminus (52). Thus, our current hypothesis is that only the NMBD directly connected to the Ma helix is prominently important for metal transport but not other metal binding domains.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the C-terminal portion of the autoinhibitory segment would be flanked by Glu 99 and Asp 170 from the transmembrane segments M1 and M2, respectively. We have previously shown that Asp 170 is a highly sensitive spot for autoinhibition and that even a conservative substitution by Asn increases the V max and the apparent affinity for Ca 2ϩ (35). Interestingly, although the basic features of the model may be shared by all autoinhibited Ca 2ϩ -ATPases, there are probably also some differences.…”
Section: Transfected K616 Cacl 2 Egtamentioning
confidence: 89%